Plastic Surgical Procedures for Lower Limb Reconstruction at a Tertiary Hospital in Nepal - Gharti Magar, Mangal; Giri, Piyush; Nagarkoti, Krishna Kumar; Karki, Bishal; Basnet, Surendra Jung; Nakarmi, Kiran Kishor; Rai, Shankar Man (Journal of Nepal Health Research Council, 2021)
Background: This study assessed the lower limb reconstruction outcome so that it will provide a baseline evidence to enable data-driven decision making to improve outcome in the future.Methods: In this study, hospital records from 1st January to 31st December 2019 were collected retrospectively. Complete data of all patients’ records treated for lower limb defects at Kirtipur Hospital were included and incomplete data were excluded. Univariate and Bivariate analyses were performedResults: In total 110 patients were included in this study with a male predominance of 66.4% (n=73). The mean age of the patients was 38.7 years (+/- 20). The majority of the patients were from outside Kathmandu valley 79.1% (n=87) and referred 55.5% (n=61). The commonest cause of lower limb defects was trauma 69.1% (n=76), the procedure performed was skin graft 48.5% (n=72), and complication was wound infections, 43% (n=13) of total complications. The hospital stay of more than two weeks was more common among the referred patients 63.9% (n=39) as compared to non-referred patients 30.6% (n=15) and trauma etiology 34.2% (n=26) had more complications than other etiology. The mean age of patients with complications (32.4 years) was lower than those without complications (41.1 years). More number of referred patients (n=43) required multiple surgeries than non-referred patients (n=21).Conclusions: Referred cases were more likely to have multiple surgeries and a longer hospital stay than non-referred cases. Infection was the commonest complication and the majority of complications were seen in trauma and younger age group. Keywords: Lower limb defect; plastic surgery; reconstruction